THE IMPORTANCE OF CUSTOMER RELATIONSHIP MARKETING TO PARTICIPANT LOYALTY THROUGH PARTICIPANT SATISFACTION IN BUSINESS ENTITIES: AN EMPERICAL STUDY IN HEALTH PROVIDER BPJS JAMBI CITY - Lidya Pusparina Sirait; Syahmardi Yacob; Agus Solikhin (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
BPJS Health as a provider of Health Insurance in Indonesia should increase service business efforts to increase customer loyalty. Especially in the competition in the insurance industry from time to time which is increasing competitive. One of the steps that can be taken is through increasing Customer Relationship Marketing which is expected to increase participant satisfaction. This study aims to analyze the effect of the variable Customer Relationship Marketing, on participant loyalty through the satisfaction of BPJS Health Business Entity Participants in Jambi City. The sample used was 100 PICs from business entities registered with BPJS Health Jambi City. The analytical tool used is SEM PLS. The results of the study found that Customer Relationship Marketing had a positive and significant effect on Participant Satisfaction, Based on the results of this study, it can be recommended that BPJS Health can maintain and develop their Customer Relationship Marketing again. So that the satisfaction and loyalty of participants can be increased.